Addition of intramuscular progesterone to vaginal progesterone in hormone replacement therapy in vitrified–warmed blastocyst transfer cycles. Issue 6 (June 2020) - Polat, Mehtap; Mumusoglu, Sezcan; Bozdag, Gurkan; Ozbek, Irem Yarali; Humaidan, Peter; Yarali, Hakan
Abstract: Research question: Does intramuscular progesterone supplementation ensure ongoing pregnancy rates (OPR) comparable with vaginal progesterone only in hormone replacement therapy cycles for vitrified–warmed embryo transfer; and is there a window of serum progesterone concentration out of which reproductive outcomes may be negatively affected? Design: Retrospective longitudinal cohort study carried out at a single IVF clinic. In total, 475 consecutive, day-5 to day-6 vitrified–warmed embryo transfer cycles using hormone replacement therapy regimen were included. Vaginal progesterone only was given to 143 patients; supplementation of vaginal progesterone only with intramuscular progesterone supplementation every third day was given to 332 patients. On the sixth day of progesterone administration, immediately before frozen–thawed embryo transfer, circulating progesterone levels were measured. Main outcome measure was OPR. Results: The baseline demographic features and embryological data of the vaginal progesterone only and intramuscular progesterone supplementation groups were comparable. The OPR were 48.3% and 51.8%, respectively ( P = 0.477). Neither the circulating progesterone level nor the type of progesterone administration were independent predictors of OPR. The effect of serum progesterone levels on OPR was evaluated by percentiles (<10%, 10–49%, 50–90% and >90%), taking 50–90% as the reference sub-group. All percentiles in the intramuscular progesterone supplementation group and in the vaginal progesterone only group had similar OPR. Conclusions: Intramuscular progesterone supplementation every third day, overall, does not enhance OPR compared with vaginal progesterone only.